ASSESSMENT OF KNOWLEDGE AND ATTITUDES TOWARD COMPLEMENTARY AND ALTERNATIVE MEDICINE (CAM) AMONGST TURKISH MEDICAL FACULTY STUDENTS - YURTSEVEN, Eray; Vehid, Suphi; Bosat, Merve; SÃ¼mer, Esin Cetinkaya; Akdeniz, SÄ±dÄ±ka ipek; CÄ±ÄŸ, GÃ¼lnaz; Tahirbegolli, Bernard (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Complementary and Alternative Medicine (CAM) therapies are becoming increasingly acceptable to the general public and areincreasingly used around the world. The international rise in focus on CAM and the increased incorporation of CAM into medical curricula,make it important to gain insight into the knowledge and attitudes of medical students about CAM and its integration in the medical curriculum.Materials and Methods: In this present study, we attempt to investigate the Cerrahpasa medical faculty students’ knowledge, attitude andpractices of the on CAM. The study used a primary cross-sectional data collection from students of Cerrahpasa Medical Faculty, IstanbulUniversity, in 2012-2013 academic years.Results: Students knowledge of CAM between classes was also compared. There were also statistically significant differences about theknowledge of those methods (acupuncture, acupressure, yoga, reiki, prayer, meditation massage, dietary, spa). Prayer was the most knownmodality in all medical classes’ students (first year students: 254, sixth year students: 192). The students who participated in the study stated that433 (%59.4) have some knowledge about the acupuncture (first year students: 229, sixth year students: 204). Acupressure was found to be atleast known methods for CAM (first year students: 313, sixth year students: 282).Conclusion: Medical students in our faculty also had limited knowledge about CAM therapies. Medical students also have an understanding ofthe importance of CAM education in the medical curriculum, specifically how it will positively influence professional attitude and stimulate thedoctor–patient relationship.